Faktor-Faktor yang Memengaruhi Kesejahteraan Mustahiq Dalam Pendayagunaan Zakat Produktif Pada Laznas Yatim Mandiri Surabaya - Meivin Ilhaniyah , Syelin Rosalina; Anwar, Moch. Khoirul (Universitas Negeri Surabaya, 2019)
This research aimed to test the factors that influence welfare mustahiq of productive zakat utilization at Laznas Yatim Mandiri Surabaya (perceptions of the adequacy of productive zakat assistance, quality of age mustahiq, family interests, mentoring and guidance, and duration of business). The method used is associative quantitative. The samples of the research were 31 mustahiq with a purposive sampling technique. The analysis technique used is multiple linier regression. The result of this research showed that partially, the perception of the duration of business had a significant effect to the welfare of mustahiq Laznas Yatim Mandiri Surabaya and simultaneously perceptions of the adequacy of productive zakat assistance, quality of age mustahiq, family interests, mentoring and guidance, duration of business had a significant effect to the welfare of mustahiq Laznas Yatim Mandiri Surabaya.